STRUCTURE REFORM AND REGULATORY SIMPLIFICATION: STRATEGIES TO ENHANCE NATIONAL ECONOMIC COMPETITIVENESS THROUGH LITERATURE REVIEW - Loso Judijanto; Al-Amin (INTERNATIONAL JOURNAL OF FINANCIAL ECONOMICS, 2025)
This study aims to analyse the strategy of structural reform and regulatory simplification as an effort to improve national economic competitiveness through a literature review. Regulatory reform and institutional restructuring are important agendas in creating a conducive business climate, overcoming overlapping regulations, and accelerating licensing and investment processes. This study uses a descriptive qualitative approach by reviewing various secondary sources, such as scientific journals, policy documents, and related research reports. The results show that regulatory simplification, digitalisation of public services, and policy harmonisation between the central and regional governments can improve the ease of doing business, attract investment, and encourage inclusive economic growth. However, challenges such as bureaucratic resistance, unsynchronised regulations, and limited institutional capacity still need to be overcome through strong political commitment, stakeholder participation, and regular regulatory evaluation to remain relevant to national and global economic dynamics.